Flipped classroom strategy and Saudi secondary students' grammar proficiency - AlQout, Abeer Mohammed; Alhamami, Munassir (Universitas Muhammadiyah Malang, 2024)
This study investigated the impact of FC on Saudi secondary school students' grammar proficiency. The participants in this study were 61 Saudi female students from the second level of secondary school. The participants were divided into two groups: the control group consisted of 30 students, and the experimental group consisted of 31 students. The control group was taught using the traditional method of instruction, while the experimental group was taught using FC. The data collection instrument was a pretest and posttest that were designed by the researchers. The pretest was administered at the beginning of the intervention, and the posttest was administered after a period of four weeks. The data from the pretest and posttest were analyzed quantitatively. The findings of the study revealed that FC did not have a significant impact on students' performance in grammar. There was no statistical difference between the scores of the students in both groups in the posttest. This study contributes to the existing literature on FC by providing evidence that FC does not have a significant impact on students' performance in grammar. One explanation is the potential mismatch between the self-directed nature of online education and the level of maturity and discipline typically expected from high school students. Also, other factors, such as the quality of the instructional materials and the teacher's pedagogical skills, may be more important than FC in improving students' grammar proficiency.